2015
DOI: 10.1016/j.ejpoleco.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Fertility choice and financial development

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…Recently, Basso et al (2014) have shown that the presence of a bank and the degree of financial development in a given county are strongly associated with lower children-towomen ratios. Using data for 78 countries over the period 1995-2010, Filoso and Papagni (2015) find that credit availability increases fertility, while access to capital market decreases fertility. However, the net effect of financial variables is positive since credit Fertility and Financial Development in South Asia availability increases fertility much more than access to capital markets reduces it.…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Basso et al (2014) have shown that the presence of a bank and the degree of financial development in a given county are strongly associated with lower children-towomen ratios. Using data for 78 countries over the period 1995-2010, Filoso and Papagni (2015) find that credit availability increases fertility, while access to capital market decreases fertility. However, the net effect of financial variables is positive since credit Fertility and Financial Development in South Asia availability increases fertility much more than access to capital markets reduces it.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, the magnitude of this decline is different in different countries. The decline in fertility is high in developed countries compared to developing countries (Filoso and Papagni 2015). This decrease in fertility has been analyzed both in economics and demography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past few decades, the rate of fertility has dramatically reduced in all the countries worldwide. However, the magnitude of such a decline varies in various countries (1). Early menopause and abnormal early infertility can affect self-efficacy and self-esteem (2).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when faced with a health-related shock, Mexican households with at least one member living in the US did not resort to borrowing, but instead relied on remittance inflows. Easier access to this informal source of credit (or credit expansion) also allows for greater incentives for debt accumulation to invest in more children as a hedge against future bad times [5]. Receiving households use these current remittance flows, from the first household members who emigrated, to invest in more children who will in turn offer old-age support for the remaining household members.…”
Section: Normal Goods and Inferior Goodsmentioning
confidence: 99%